Peran Green Trust dan Theory Planned Behavior pada Konsumerisme Produk Hijau - Tara C. Abraham; Farbi Nasa; Hendrik P. P. Mursid; Anastasia B. Hotmaduma; Hanifan Fajar (Indonesian Business Review, 2022)
Understanding of green buying behavior among general consumers in urban cities Indonesia is the important foundation for green marketing. This study aims to examine the determining factors and their significance in predicting the behavior. From 278 data gathered from online questionnaire that spread to respondent, which domiciled in Jakarta Greater Area, only 265 data are eligible to use for conduct analysis. Consist of 28 items, factor analysis is used to corroborate the reliability and validity of the questionnaire and sample adequacy is used prior to ensuring factor analysis. To test the hypothesis, data studies are tested using regression analysis. Findings confirm that Environmental Concern, Personal Norms, Willingness to Pay Premium, and Green Trust relate positively to Green Purchase Intention and Perceived Value as the substantial predictor variable.